Linguistic Foundations of Identity: Readings in Language, Literature and Contemporary Cultures - Om Prakash and Rajesh Kumar (Aakar Books, 2018)
The collection of papers in this book brings together researchers working in paradoxes and complexities of cultural identities through uses of language and literature.